Basic values predict doping likelihood. Issue 4 (16th February 2020) - Ring, Christopher; Kavussanu, Maria; Gürpınar, Bahri
ABSTRACT: Basic values, defined as trans-situational goals that vary in importance and act as guiding principles in life, have been linked with unethical cognitions, emotions and actions. Their roles in doping, a form of cheating in sport, have yet to established. College athletes reported doping likelihood in hypothetical scenario-based situations and completed measures of basic values, moral disengagement, and anticipated guilt. Correlation analysis showed that doping likelihood was positively associated with self-enhancement values but negatively associated with self-transcendence values and conservation values. Moral disengagement correlated positively with self-enhancement values and negatively with self-transcendence values, whereas guilt correlated positively conservation values and negatively with self-enhancement values and openness to change values. Regression analyses showed that self-enhancement values positively predicted doping likelihood directly, self-transcendence values negatively predicted doping likelihood indirectly via moral disengagement and guilt, and conservation values negatively predicted doping likelihood indirectly via guilt. In line with theory and evidence concerning the relationship between basic value systems and moral thought and action, we found that the values of athletes are directly (self-enhancement) and indirectly (self-transcendence, conservation) linked with likely use of banned performance enhancing substances, an expression of cheating in sport.